Plasma metal silicon composite nanostructure catalyst and preparation method and application thereof

By modifying Si-H bonds and alkyl chains on a silicon substrate, a plasma-modified metal-silicon composite nanostructure catalyst was developed, which solved the problems of poor carrier separation and the influence of chemical residues. This resulted in highly efficient photocatalytic performance and stable catalyst dispersion, making it suitable for photocatalytic carbon dioxide reduction and hydrogen production reactions.

CN119281384APending Publication Date: 2025-01-10SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411418268.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing plasma-based metal nanoparticle and semiconductor composite materials suffer from poor carrier separation and chemical residues in terms of catalytic activity, and the synthesis process is complex and time-consuming.

Method used

A plasma-modified metal-silicon composite nanostructure catalyst with Si-H bonds and alkyl chains on a silicon substrate surface is used to disperse silicon nanocrystals and metal nanoparticles on the silicon substrate surface through electrostatic adsorption. By utilizing the reducing properties of silicon nanocrystals, surface-exposed PMNPs can be prepared without additional chemical agents, achieving stable dispersion and protection.

Benefits of technology

The synthesis process was simplified, the carrier separation efficiency and catalytic activity were improved, and the catalyst showed high efficiency and stability in photocatalytic carbon dioxide reduction and hydrogen production, and has the potential for commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005080038550000011
    Figure HDA0005080038550000011
  • Figure HDA0005080038550000012
    Figure HDA0005080038550000012
  • Figure HDA0005080038550000013
    Figure HDA0005080038550000013
Patent Text Reader

Abstract

The invention discloses a plasma metal silicon composite nanostructure catalyst and a preparation method and application thereof, the plasma metal silicon composite nanostructure catalyst comprises a silicon substrate, silicon nanocrystals and metal nanoparticles, the silicon nanocrystals and the metal nanoparticles are loaded on the silicon substrate, and the surface of the silicon substrate is modified with Si-H bonds and alkyl chains. The synthesis method of the plasma metal silicon composite nanostructure catalyst is simple, the yield is high and stable, and additional reagents and auxiliary materials do not need to be added. The plasma metal silicon composite nanostructure catalyst has extremely high application prospects in the fields of heterogeneous photocatalytic carbon dioxide reduction, photocatalytic hydrogen production, carbon dioxide photocatalytic conversion, most organic catalytic reactions and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a plasma metal silicon composite nanostructured catalyst and a preparation method and application thereof. Background Art

[0002] Plasmonic metals (PMs) can produce localized surface plasmon resonance (LSPR) effects in the visible and even near-infrared spectral range, which gives plasmonic metals significantly enhanced light-harvesting capabilities, thus endowing plasmonic nanoparticles (PMNPs) with good prospects as photocatalysts. Since the beginning of this century, the nanostructures of plasmonic metals have been widely studied in the field of heterogeneous catalysis. This interest stems from their unique physicochemical properties compared to bulk metals, including morphology effects, mild reaction conditions, and relatively low cost and toxicity compared to other precious metals.

[0003] However, plasmonic metal nanoparticles (PMNPs) often face the dilemma of insufficient catalytic activity due to the loss of hot electrons due to ultrafast electron-electron scattering. Combining plasmonic metal nanoparticles with semiconductors is an effective strategy to utilize more photogenerated electrons to address this problem. Plasmon-induced interfacial charge transfer can excite and transfer electrons from metals to semiconductors. The Schottky barriers in such composites can promote the migration of charge carriers and reduce carrier recombination, thereby improving the catalytic efficiency. However, the strong competition between hot electron transfer and ultrafast electron-electron scattering remains a major challenge. In addition, the weak electronic interaction between these materials causes the photoexcited charge carriers to be confined to the semiconductor or PMNPs surface, limiting the practical applications of many semiconductor-metal composites.

[0004] There have been some reports on the construction of composite materials of plasma metal nanoparticles (PMNPs) and semiconductor substrates. However, the ability of these substrate materials to receive carriers is limited, resulting in poor carrier separation, which in turn affects the catalytic activity. In addition, in order to stabilize PMNPs particles, additional chemical stabilizers and reducing agents are often used in the synthesis process. These chemicals may remain on the surface of the particles, reducing effective adsorption sites and affecting carrier transport, thereby hindering catalytic performance. Although there have been some reports trying to remove chemical residues on PMNPs, the operation is usually complicated and time-consuming. Therefore, developing a simple synthesis method to prepare plasma metal / semiconductor composites, while obtaining PMNPs with exposed surfaces and combining them with the desired semiconductor substrate, has become a research focus in the field of efficient plasma catalysis. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a plasma metal silicon composite nanostructured catalyst and a preparation method and application thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a plasma metal silicon composite nanostructure catalyst, comprising a silicon substrate, silicon nanocrystals and metal nanoparticles supported on the silicon substrate, wherein the surface of the silicon substrate is modified with Si-H bonds and alkyl chains.

[0008] In the present invention, the alkyl chains on the surface of the silicon substrate have a confining effect, and can disperse silicon nanocrystals and metal nanoparticles in the space region formed by the ligands on the surface of the silicon substrate through electrostatic adsorption, and can also stabilize and protect the nanocatalyst.

[0009] In some embodiments of the present invention, the silicon substrate is a substrate formed by at least partially covering silicon nanocrystals with silicon dioxide.

[0010] In some embodiments of the present invention, the metal nanoparticles include at least one of gold, silver, copper, aluminum, platinum, and palladium nanoparticles.

[0011] In some embodiments of the present invention, the alkyl chain comprises C6 to C 35 Alkyl chains, such as octadecyl chain, decadecyl chain, dodecyl chain, tetradecyl chain, hexadecyl chain, octadecyl chain, eicosyl chain, docosyl chain, pentacosyl chain, triacontyl chain, and the like.

[0012] In some embodiments of the present invention, the molar ratio of the metal nanoparticles to silicon is 0.1 to 0.2:1.

[0013] In some embodiments of the present invention, the molar ratio of the silicon substrate to the alkyl chain is 20-50:1-0.5.

[0014] In some embodiments of the present invention, the particle size of the silicon substrate is 60-120 nm.

[0015] In some embodiments of the present invention, the average particle size of the metal nanoparticles is 2 to 12 nm.

[0016] In some embodiments of the present invention, the average particle size of the silicon nanocrystals is 2 to 8 nm.

[0017] In some embodiments of the present invention, the plasma metal silicon composite nanostructured catalyst is in at least one of a spherical shape, a rod shape, a plate shape, a disc shape or a cone shape; and its particle size is 60 nm to 100 μm.

[0018] The second aspect of the present invention provides a method for preparing the plasma metal silicon composite nanostructured catalyst, comprising the following steps:

[0019] The silicon substrate is etched to obtain silicon nanoparticles with silicon-hydrogen bonds on the surface, and then 35 After the olefin undergoes an addition reaction and then undergoes a reduction reaction with a metal salt, the plasma metal silicon composite nanostructure catalyst is obtained.

[0020] In some embodiments of the present invention, the method for preparing the silicon substrate comprises the following steps: subjecting a silane compound to a hydrolysis reaction to obtain a silicon nanoparticle precursor, and then subjecting a solid phase oxidation-reduction reaction to obtain the silicon substrate.

[0021] In some embodiments of the present invention, the addition reaction, reduction reaction, hydrolysis reaction, and solid phase redox reaction are all carried out under a protective atmosphere and in response to external stimuli.

[0022] In some embodiments of the present invention, the protective atmosphere includes at least one of nitrogen, argon, oxygen and carbon dioxide.

[0023] In some embodiments of the present invention, the external stimulus response includes at least one of light stimulation, temperature stimulation, acid-base stimulation, chemical initiation or catalytic stimulation, electric field stimulation, magnetic field stimulation, ultrasound stimulation or biological function analysis stimulation.

[0024] In some embodiments of the present invention, when the external stimulus response is light stimulation, the wavelength of the light source used for the light stimulation is 350-650nm, and the power is 1-100W; when the external stimulus response is temperature stimulation, the temperature of the temperature stimulation is 25-1200℃, such as 100℃, 110℃, 150℃, 500℃, 800℃, 900℃, etc.; when the external stimulus is acid-base stimulation, the pH of the acid-base stimulation is 0.1-4 or 10-13; when the external stimulus is chemical initiation or catalytic stimulation, the initiator or catalyst is at least one of azobisisoheptanonitrile, azobisisobutyronitrile, benzoyl peroxide, cyclohexanone peroxide, tert-butyl hydroperoxide, palladium and rhodium.

[0025] In some embodiments of the present invention, the reducing agent of the solid phase redox reaction is hydrogen or a metal, such as sodium, magnesium, or lithium.

[0026] In some embodiments of the present invention, the concentration of the metal salt is 0.1 to 2 mg / mL. If the concentration of the plasma metal compound is too low, the number of plasma metal nanoparticles will be too small, resulting in insufficient LSPR effect and thus affecting its catalytic performance. If the concentration is too high, the reaction may be too intense, causing the silicon nanocrystals to be oxidized into silicon dioxide, making it difficult to obtain a suitable plasma metal silicon composite nanostructure catalyst.

[0027] In some embodiments of the present invention, the silicon substrate can be prepared according to conventional methods in the art; it can also be prepared according to the method described below, and the preparation method of the silicon substrate comprises the following steps: under a protective atmosphere and in response to external stimuli, mixing a silane compound, water and an alcohol, stirring until solidification, aging for 8 to 48 hours, and drying at 60 to 120° C. for 1 to 24 hours to obtain a hydrogel; subjecting the hydrogel to a solid-phase redox reaction in hydrogen and a protective atmosphere, the reaction temperature is 400 to 1600° C., the reaction time is 30 minutes to 24 hours, and the volume fraction of hydrogen is 1 to 30%, to obtain the substrate.

[0028] In some embodiments of the present invention, in the solid-phase redox reaction, if the volume fraction of hydrogen is too large, it may cause safety risks, while if the volume fraction is too small, the reducing property may be insufficient, which may affect the number and properties of silicon nanocrystals in the obtained composite.

[0029] In some embodiments of the present invention, the silane compound includes at least one of tetramethoxysilane, tetraethoxysilane, trimethoxysilane, triethoxysilane, methyltrimethoxysilane and ethyltrimethoxysilane.

[0030] The third aspect of the present invention provides an application of the plasma metal silicon composite nanostructured catalyst in an organic catalytic reaction.

[0031] In some embodiments of the present invention, the organic catalytic reaction includes any one of a photocatalytic carbon dioxide reduction reaction and a photocatalytic hydrogen production reaction.

[0032] The beneficial effects of the present invention are:

[0033] (1) The present invention adopts a strategy of surface chemical confinement synthesis, controls the degree of surface functionalization of silicon nanocrystals, and prepares PMNPs with bare surface through in-situ reaction on this basis. Silicon nanocrystals with Si-H bonds and alkyl chains on the surface can reduce metal ions to metal nanoparticles by virtue of the reducing property of Si-H bonds, and at the same time, utilize the confinement effect of the surface alkyl chains to disperse the metal nanoparticles in the space region formed by the surface ligands, wherein some silicon nanocrystals will be oxidized to silicon dioxide, forming a substrate and loading silicon nanocrystals and metal nanoparticles through electrostatic adsorption, playing a role in stabilizing and protecting the nanocatalyst. The present invention utilizes the reducing property of silicon nanocrystals themselves for the first time, and realizes the process of target plasma metal nanoparticles on the surface of silicon nanocrystals from reduction to controllable growth and then co-dispersion through fine surface chemical regulation. This method does not add any additional chemical reducing agents and stabilizers, and the PMNPs with bare surface can be stably dispersed in the solution with silicon nanocrystals.

[0034] (2) The synthesis method of the plasma metal silicon composite nanostructured catalyst of the present invention is simple, with high and stable yield, and does not require the addition of additional reagents and auxiliary materials. The plasma metal silicon composite nanostructured catalyst has extremely high application prospects in the fields of heterogeneous photocatalytic carbon dioxide reduction, photocatalytic hydrogen production, carbon dioxide photocatalytic conversion and most organic catalytic reactions. For example, under the conditions of carbon dioxide photocatalytic reduction, the catalyst can produce 1552 μmol / g of carbon monoxide within 6 hours while maintaining 100% selectivity. The product yield can be regulated by changing the catalyst synthesis, catalytic reaction conditions and feed ratio, providing a potential commercial method for plasma metal nanocatalysis to help achieve the "dual carbon" goal. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the synthesis route of the silver / silicon composite nanostructured catalyst powder prepared in Example 1.

[0036] Figure 2 This is a physical photograph of the silver / silicon composite nanostructured catalyst colloid dispersion prepared in Example 1.

[0037] Figure 3 The structure and property characterization of the silver / silicon composite nanostructured catalyst prepared in Example 1; wherein a is the XRD diffraction spectrum before and after the catalyst preparation reaction, b is the FTIR spectrum before and after the catalyst preparation reaction, and c is the XPS spectrum before and after the catalyst preparation reaction.

[0038] Figure 4 Transmission electron microscope images of the unfunctionalized silicon nanocrystals (a) and the functionalized silicon nanocrystals (b) used in Example 1 to prepare the silver / silicon composite nanostructure catalyst.

[0039] Figure 5 Bright field and dark field high-resolution transmission electron microscope images of the silver / silicon composite nanostructure catalyst prepared using functionalized silicon nanocrystals in Example 1.

[0040] Figure 6 The statistical results of particle size analysis of silver nanoparticles (a) and silicon nanocrystals (b) in Example 1 are shown.

[0041] Figure 7 Energy dispersive X-ray spectra (EDX) of silver / silicon composite nanostructured catalysts of different sizes prepared using functionalized silicon nanocrystals in Example 1.

[0042] Figure 8 The UV-visible absorption spectra (UV) and steady-state fluorescence (PL) spectra of the functionalized silicon nanocrystals and the silver / silicon composite nanostructure catalyst in Example 1 are shown.

[0043] Fig. 9 This is a data graph showing the photocatalytic reduction performance of carbon dioxide of functionalized silicon nanocrystals and silver / silicon composite nanostructure catalysts in experimental group 1 within 6 hours.

[0044] Fig.10 The amount of silver / silicon composite nanostructured catalyst prepared in Example 1 (a), the silver / silicon ratio of the catalysts in Example 2 and Example 3 (b), and the effect of different alkyl chain surface modifications in Example 1 and Example 4 on the performance of carbon dioxide photocatalytic reduction.

[0045] Fig.11 The UV-visible absorption spectra (UV) of the composite nanostructured catalysts with different silver / silicon ratios in Example 1 are shown.

[0046] Fig.12 The silver / silicon composite nanostructure catalyst prepared in Example 3 is 13 Analysis of gas phase mass spectrometry products of carbon dioxide photocatalytic reduction under CO2 atmosphere. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0048] Example 1

[0049] In this embodiment, a silver / silicon composite nanostructured catalyst is prepared. The preparation process diagram is shown in FIG. Figure 1 As shown, the specific process is:

[0050] S1: Under a nitrogen atmosphere, trimethoxysilane (24 mL), isopropanol (16 mL), water (20 mL), acetonitrile (20 mL), and nitric acid (48 mmol) were added to a round-bottom flask and mixed. After stirring until the system was completely dissolved, the mixture was heated at 120 °C and continued to stir. When the system was gelled and completely solidified, stirring was stopped. After aging for 48 h, the mixture was washed with deionized water and ethanol for 3 times respectively, dried in an oven at 105 °C for 24 hours, taken out, and ground into fine white powder to obtain a uniform hydrolyzed gel (HSiO x );

[0051] S2: Dry the completely HSiO x Place it in a tube furnace and heat it at 1100℃ for 3h in a mixed atmosphere of hydrogen and argon. After cooling, pre-grind it with an agate mortar and then add it to a ball mill for ball milling to obtain a dark brown powder Si@SiO x , which is a substrate composite that wraps silicon nanoparticles.

[0052] S3: grinding the substrate complex encapsulating the nanoparticles to a particle size of 60 to 120 nm, and then dispersing the nanoparticles in an etching solution, reacting for 10 min to 2 h, and then extracting with a hydrophobic organic solvent, centrifuging, and washing to obtain silicon nanoparticles with silicon-hydrogen bonds modified on the surface;

[0053] S4: Under the protection of inert gas, silicon nanoparticles with silicon-hydrogen bonds on the surface are mixed with octadecene, and cyclohexanone peroxide is added to react under heating conditions to obtain functionalized silicon nanocrystals alkyl-SiNCs. Then, an appropriate amount of silver chlorate is added and stirred at room temperature for 10 minutes to 2 hours to obtain the silver / silicon composite nanostructure catalyst Ag@alkly-SiNCs. The actual picture is as follows Figure 2 shown.

[0054] In S4, the amount of silver chlorate added was controlled to prepare silver / silicon composite nanostructured catalysts Ag@alkly-SiNCs with silver mass fractions of 2%, 5%, and 10%, respectively.

[0055] Example 2

[0056] This example prepares a silver / silicon composite nanostructured catalyst, and the specific process is as follows:

[0057] The amount of trimethoxysilane in Example 1 was doubled to 48 mL, and the other raw materials and their amounts were set exactly as in Example 1. Then, silver / silicon composite nanostructured catalysts with different silver-silicon ratios were prepared according to exactly the same preparation method and steps as in Example 1.

[0058] Example 3

[0059] This example prepares a silver / silicon composite nanostructured catalyst, and the specific process is as follows:

[0060] The amount of trimethoxysilane in Example 1 was increased to 5 times, that is, 120 mL was used, and the other raw materials and their amounts were set exactly as in Example 1. Then, silver / silicon composite nanostructured catalysts with different silver-silicon ratios were prepared according to exactly the same preparation method and steps as in Example 1.

[0061] Example 4

[0062] This example prepares a silver / silicon composite nanostructured catalyst, and the specific process is as follows:

[0063] The silicon nanoparticles with silicon-hydrogen bond modification on the surface in step 4 of Example 1 were mixed with dodecene, and the other raw materials and their amounts were completely set according to Example 1. Then, silver / silicon composite nanostructured catalysts with different surface alkyl chain modifications were prepared according to the same preparation method and steps as in Example 1.

[0064] Test Example 1

[0065] The catalyst was structurally analyzed and the results are as follows: Figure 3 As shown, a is the XRD diffraction pattern before and after the catalyst preparation reaction. The crystal diffraction peaks from top to bottom represent the unfunctionalized silicon nanocrystals, the unfunctionalized silicon nanocrystals after reacting with silver ions, the functionalized silicon nanocrystals, and the functionalized silicon nanocrystals after reacting with silver ions. The diffraction peaks of 28.2°, 47.2°, and 56.5° in the XRD diffraction pattern represent the (111), (220), and (311) crystal planes of the silicon crystals, respectively, which are consistent with the standard XRD pattern, indicating that the silicon nanocrystals have been successfully prepared and their crystal structure has not been destroyed. After the unfunctionalized silicon nanocrystals reacted with silver ions, the characteristic diffraction peaks of the silicon crystals above all disappeared, and were replaced by the characteristic peaks of elemental silver and silver oxide, which indicates that although the silver ions were successfully reduced, the crystal structure of the silicon nanocrystals was destroyed. When the functionalized silicon nanocrystals were used for the reaction, the X-ray diffraction results of the obtained product showed that the structure of the silicon nanocrystals was not destroyed, and the silicon nanocrystals and the reduced silver nanoparticles coexisted. b is the FTIR spectrum before and after the catalyst preparation reaction. The results indicate that the silicon-hydrogen bonds on the surface of the silicon nanocrystals are the key source of reduced silver ions. After the reaction, other functionalized ligands on the surface did not change. c is the XPS spectrum before and after the catalyst preparation reaction, which also shows that the silicon nanocrystals still exist after the preparation reaction, and the silver nanoparticles are successfully prepared.

[0066] The catalyst was characterized by high resolution transmission electron microscopy (HRTEM). Figures 4 to 6 As shown, Figure 4The differences in morphology and size of the products obtained by preparing the catalyst using unfunctionalized and functionalized silicon nanocrystals are reflected. Figure 5 To observe the image of silver / silicon composite nanostructured catalyst at higher resolution, the distribution of particles and different lattice constant data were obtained. Figure 6 These are the statistical results of particle size analysis of silver nanoparticles and silicon nanocrystals respectively. Figure 7 The distribution of different elements in the catalyst was collected through energy dispersive X-ray spectroscopy, reflecting the co-dispersion state of silicon nanocrystals and silver nanoparticles.

[0067] The above results show that the present invention has prepared a catalyst having a composite nanostructure of plasma metal and crystalline silicon. The uniform structure of plasma metal nanoparticles and semiconductor nanoparticles in the catalyst is conducive to generating more photogenerated electrons and promoting carrier migration, such as Figure 8 As shown, the catalyst has significantly enhanced light absorption, and its fluorescence quenching indicates that the recombination of carriers is suppressed, thereby improving the efficiency of carrier separation and facilitating the catalytic reaction. At the same time, the good colloidal dispersion of the catalyst improves the contact between the catalyst interface and the reactants, providing a chemical environment for homogeneous reactions while having the advantages of heterogeneous catalysis, making the catalyst material have great application potential in the field of plasma metal catalysis.

[0068] Example 5

[0069] In this example, the catalysts prepared in Examples 1 to 4 were subjected to a photocatalytic reduction of carbon dioxide experiment, and the specific process was as follows:

[0070] 2 mg of the silver / silicon composite nanostructured catalyst Ag@alkly-SiNCs prepared in Example 1 was weighed into a quartz reaction bottle, 10 mL of dimethylformamide (DMF) and 5 mL of deionized water were added to the bottle, a magnetic stirrer was added and the bottle mouth was sealed with a rubber stopper, 99.999% CO2 was introduced into the reaction bottle through a connected syringe for half an hour, and then the reaction bottle filled with CO2 was loaded into a photocatalytic reactor for light catalytic reaction. After the reaction time was over, 100 μL of the gas in the bottle was taken and the gas components were analyzed by GC, and the carbon monoxide content was obtained by fitting calculation. The result is shown as follows: Fig. 9 Then, according to the above steps, the silver / silicon composite nanostructured catalysts prepared in Example 2, Example 3 and Example 4 were used for photocatalytic reduction of carbon dioxide, and the results were as follows: Fig.10As shown, wherein a is the effect of the amount of the silver / silicon composite nanostructured catalyst prepared in Example 1 on the catalytic performance, b is the catalytic performance data of the silver / silicon composite nanostructured catalysts with different silver-silicon ratios prepared in Examples 2 and 3 while maintaining the catalyst amount, reaction conditions and reaction time, and c is the catalytic performance data of the silver / silicon composite nanostructured catalyst modified with a dodecyl chain prepared in Example 4 while maintaining the catalyst amount, reaction conditions and reaction time, compared with the silver / silicon composite nanostructured catalyst modified with an octadecyl chain prepared in Example 1.

[0071] Depend on Fig.11 It can be seen that the performance improvement of the composite nanostructured catalyst prepared by the present invention is significantly related to the enhanced LSPR characteristic absorption. Fig.12 It can be seen that the photocatalytic reduction product CO using this catalyst is completely derived from CO2.

[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A plasma metal silicon composite nanostructured catalyst, characterized in that: The invention comprises a silicon substrate, silicon nanocrystals and metal nanoparticles loaded on the silicon substrate, and the surface of the silicon substrate is modified with Si-H bonds and alkyl chains.

2. The plasma metal silicon composite nanostructured catalyst according to claim 1, characterized in that: The silicon substrate is a substrate formed by at least partially covering silicon nanocrystals with silicon dioxide.

3. The plasma metal silicon composite nanostructured catalyst according to claim 1, characterized in that: The metal nanoparticles include at least one of gold, silver, copper, aluminum, platinum and palladium nanoparticles.

4. The plasma metal silicon composite nanostructure catalyst according to claim 1, characterized in that: The alkyl chain includes C6~C 35 Alkyl chain.

5. The plasma metal silicon composite nanostructured catalyst according to claim 1, characterized in that: The molar ratio of the metal nanoparticles to silicon is 0.1-0.2:

1.

6. A method for preparing the plasma metal silicon composite nanostructured catalyst according to any one of claims 1 to 5, comprising the following steps: The silicon substrate is etched to obtain silicon nanoparticles with silicon-hydrogen bonds on the surface, and then 35 After the olefin undergoes an addition reaction and then undergoes a reduction reaction with a metal salt, the plasma metal silicon composite nanostructure catalyst is obtained.

7. The preparation method according to claim 6, characterized in that: The method for preparing the silicon substrate comprises the following steps: subjecting a silane compound to a hydrolysis reaction to obtain a silicon nanoparticle precursor, and then subjecting a solid phase oxidation-reduction reaction to obtain the silicon substrate.

8. The preparation method according to claim 6, characterized in that: The concentration of the metal salt is 0.1-2 mg / mL.

9. Use of the plasma metal silicon composite nanostructured catalyst according to any one of claims 1 to 5 in organic catalytic reactions.

10. The use according to claim 9, characterized in that: The organic catalytic reaction includes any one of a photocatalytic carbon dioxide reduction reaction and a photocatalytic hydrogen production reaction.